1998
DOI: 10.1007/s002329900362
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Carboxy Terminal Serine Residues Stabilize the Mouse Gap Junction Protein Connexin45 Against Degradation

Abstract: Phosphoamino acid analysis of mouse connexin45 (Cx45) expressed in human HeLa cells revealed that phosphorylation occurred mainly at serine residues, but also on tyrosine and threonine residues. To characterize the role of Cx45 phosphorylation, different serine residues of the serine-rich carboxy terminal region were deleted or exchanged for other amino acids residues. Human HeLa cells deficient in gap junctional intercellular communication were stably transfected with appropriate constructs and analyzed for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…Cx45 has been shown to be phosphorylated in cells incubated with 32 Porthophosphate. Deletion of the last 26 amino acids of Cx45 (nine of which are serines) or substitution of the serines to glycine or alanine led to a 90% reduction in phosphorylation and a dramatic loss of communication in former case (Hertlein, Butterweck, Haubrich, Willecke, & Traub, 1998). Cx45 channels have also been shown to be modulated by phosphorylation .…”
Section: Phosphorylation Of Cx32 Cx40 Cx45 Cx46 and Cx50mentioning
confidence: 99%
“…Cx45 has been shown to be phosphorylated in cells incubated with 32 Porthophosphate. Deletion of the last 26 amino acids of Cx45 (nine of which are serines) or substitution of the serines to glycine or alanine led to a 90% reduction in phosphorylation and a dramatic loss of communication in former case (Hertlein, Butterweck, Haubrich, Willecke, & Traub, 1998). Cx45 channels have also been shown to be modulated by phosphorylation .…”
Section: Phosphorylation Of Cx32 Cx40 Cx45 Cx46 and Cx50mentioning
confidence: 99%
“…HeLa cells were metabolically labeled with [ 35 S]methionine for 1 h, as described by Hertlein et al (1998). Medium was replaced by nonradioactive medium, supplemented with additional 15 mg/l methionine (final concentration 45 mg/l).…”
Section: Pulse-chase Analysis and Determination Of Half-lifementioning
confidence: 99%
“…In contrast, for mouse Cx45 it has been shown that decreased phosphorylation coincided with degradation of this protein (2). The substitution of one or more serine residues for other amino acids increases degradation of the transfected Cx45 in HeLa cells (5). Since in vivo phosphorylation sites for any of the above mentioned connexins have not been mapped, the direct relationship between in vivo phosphorylation and connexin degradation is not clear.…”
mentioning
confidence: 99%
“…The COOH terminus, the most variable region among connexins, contains several putative kinase consensus sequences. The phosphorylation of connexins has been indicated in the intracellular trafficking of connexins (2), channel assembly (3), gating of gap junctional communication (4), stabilization of connexins from degradation (5,6), etc. In isolated myocardial gap junctions, most Cx43 phosphorylation sites are in the region 271-382 (7).…”
mentioning
confidence: 99%